Amelioration of gastric ulcer using a hydro-alcoholic extract of Mangifera indica in Sprague Dawley rats by prevention of muco-oxidative stress - Nazma Khan; Mohammad Khushtar; Md Azizur Rahman; Md Kaish; Mohd Ajmal (Elsevier, 2024)
Background: Gastric ulcer is a significant global public health concern that can result in severe complications such as gastro-intestinal bleeding, perforations, gastro-intestinal obstruction and cancer. Mangifera indica seed kernel, a traditional Chinese medicine, is widely available and used in China. The current study was aimed to determine gastro-protective effect of Mangifera indica kernel extract in preventing gastric ulcer in rats. Methods: SD rats were divided into six groups. Each group consisted of five rats. Group-I received 1 ml/kg/day p.o. of 1 % carboxy methylcellulose. Group-II received indomethacin (20 mg/kg/day, p.o.). Group-III received Mangifera indica kernel extract (500 mg/kg/day, p.o.). Group-IV received the extract (1000 mg/kg/day, p.o.). Group-V received 50 mg/kg/day ranitidine. Group-VI (per se) received the extract (1000 mg/kg/day, p.o.). The ulcer index, mucus barrier, and histopathology were calculated. After homogenization of gastric tissue in buffer, anti-oxidant enzyme potency was also evaluated. Results: Mangifera indica kernel extract significantly (p < 0.01) and dose-dependently increased mucus, superoxide dismutase, and catalase levels while lowered ulcer index and thiobarbituric acid reactive substances in comparison to ulcer control group-II. According to histopathological data, indomethacin medication led to gastric ulcers whereas Mangifera indica kernel extract protected from gastric ulcer by prevention of indomethacin-induced muco-oxidative stress. Mangifera indica 1000 mg/kg/day in group-IV had ulcer prevention potency comparable to ranitidine 50 mg/kg/day in group-V. Discussion: Thus, Mangifera indica extract possesses promising effect on amelioration of gastric ulcer and protects from gastric ulcer by prevention of indomethacin-induced muco-oxidative stress, re-inforcing the gastric mucosa, and reducing the secretion of gastric acid.